2017
DOI: 10.33736/ijbs.576.2015
|View full text |Cite
|
Sign up to set email alerts
|

Testing Assumptions of the “Slippery Slope Framework” Using Cross-Country Data: Evidence From Sub-Saharan Africa

Abstract: The emergence of “Slippery Slope Framework” has attracted many researchers who examined the effect of trust in authorities and power of authorities on tax compliance using both the real taxpayer and student subjects. However, these researchers have neglected the use of cross-country data to examine these effects. In line with prior empirical evidences that confirm the effect of trust and power of authorities on tax compliance, this study hypothesizes that both trust and power have association with tax complian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 15 publications
1
18
0
1
Order By: Relevance
“…In order to confirm whether or not the propositions of the Slippery Slope Framework hold in real world situations, various studies were undertaken for validation. For example, in Europe (Kastlunger, et al, 2013;Kirchler, et al, 2008;Kogler, et al, 2013;Pellizzari & Rizzi, 2014;Siglé, et al, 2018;Wahl, et al, 2010) and later Asia (Andyarini, Subroto, & Subekti, 2019;Batrancea & Nichita, 2014;Damayanti & Martono, 2018;Faizal et al, 2017;Mardhiah, Miranti & Tanton, 2019), Africa (Ayuba, Saad & Ariffin, 2018;Mas' ud, et al, 2015;Mas'ud, et al, 2014), and South America (da Silva, Guerreiro & Flores, 2019). However, most of these validations are country specific, except a few such as Mas' ud, et al, (2015) and Mas'ud, et al, (2014) that have a continental focus with emphasis on Africa.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to confirm whether or not the propositions of the Slippery Slope Framework hold in real world situations, various studies were undertaken for validation. For example, in Europe (Kastlunger, et al, 2013;Kirchler, et al, 2008;Kogler, et al, 2013;Pellizzari & Rizzi, 2014;Siglé, et al, 2018;Wahl, et al, 2010) and later Asia (Andyarini, Subroto, & Subekti, 2019;Batrancea & Nichita, 2014;Damayanti & Martono, 2018;Faizal et al, 2017;Mardhiah, Miranti & Tanton, 2019), Africa (Ayuba, Saad & Ariffin, 2018;Mas' ud, et al, 2015;Mas'ud, et al, 2014), and South America (da Silva, Guerreiro & Flores, 2019). However, most of these validations are country specific, except a few such as Mas' ud, et al, (2015) and Mas'ud, et al, (2014) that have a continental focus with emphasis on Africa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…European data in this regard was considered by (Benk & Dubak, 2011;Kastlunger, et al, 2013;Kirchler, et al, 2008;Kogler, et al, 2013;Pellizzari & Rizzi, 2014;Wahl, et al, 2010), while Asian experience was analyzed in (Andyarini, Subroto, & Subekti, 2019;Batrancea & Nichita, 2014;Faizal et al, 2017). A few studies that employed cross-country analyses were Mas' ud et al, (2015) and Mas'ud et al, (2014). However, these studies mainly focused on African states, hence, the need for global cross-country inference has motivated this paper.…”
Section: Introductionmentioning
confidence: 99%
“…However, when analysing the perception of citizens, the findings are not conclusive. Analysing previous citizen surveys, the finding is that while some confirm the effectiveness of this approach, revealing that increasing the actual and/or perceived level of deterrents reduces non-compliance (Feld and Frey, 2002;Mas'ud et al, 2015;Mazzolini et al, 2017), others found no effect (Hartl et al, 2015;Shaw et al, 2008;Franic, 2015, 2016), and yet others that increasing the actual and/or perceived level of deterrents might lead to greater non-compliance due to a breakdown of the social contract between the government and its citizens (Chang and Lai, 2004;Hofmann et al, 2017;Kaplanoglou and Rapanos, 2015;Murphy, 2005Murphy, , 2008Murphy and Harris, 2007).…”
Section: Small Business and The Policy Measures For Reducing Informalmentioning
confidence: 99%
“…However, despite the widespread adoption of this rational economic actor approach by governments, the evidence that increasing the penalties and probability of detection leads to compliance is less than conclusive. Some studies confirm that compliance is significantly higher when the levels of penalties and risks of detection are higher (Feld and Frey 2002;Mas'ud et al 2015;Mazzolini et al 2017), others find no significant association (Hartl et al 2015;Shaw et al 2008;Franic 2015, 2016), and yet others that non-compliance increases (Chang and Lai 2004;Hofmann et al 2017;Kaplanoglou and Rapano, 2015;Murphy 2005Murphy , 2008Murphy and Harris 2007). A problem specific to salary under-reporting, moreover, is that this practice is difficult for tax and labour inspectors to detect.…”
Section: Explaining and Tackling Under-declared Employment: Review Anmentioning
confidence: 99%